2015
DOI: 10.1007/s00223-015-9954-z
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet Causes Bone Loss in Young Mice by Promoting Osteoclastogenesis Through Alteration of the Bone Marrow Environment

Abstract: Obesity is a severe health problem in children, afflicting several organ systems including bone. However, the role of obesity on bone homeostasis and bone cell function in children has not been studied in detail. Here we used young mice fed a high-fat diet (HFD) to model childhood obesity and investigate the effect of HFD on the phenotype of cells within the bone marrow environment. Five-week-old male mice were fed a HFD for 3, 6, and 12 weeks. Decreased bone volume was detected after 3 weeks of HFD treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
79
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(98 citation statements)
references
References 43 publications
15
79
3
1
Order By: Relevance
“…In addition to altered trabecular bone properties with HF, here, we also observed a negative impact of HF on the cortical femur including decreased cortical thickness and TMD. The effects of high-fat feeding on trabecular bone observed in our study were modest compared to changes reported by others [12, 13, 32]. We speculate that some of the differences between studies may be accounted for by specific aspects of the diet (e.g., 45% fat content vs. 60%), differences in species (e.g., rat vs. mouse), or differences in genetic makeup within a species (e.g., BALB/c vs C57BL/6 mice).…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…In addition to altered trabecular bone properties with HF, here, we also observed a negative impact of HF on the cortical femur including decreased cortical thickness and TMD. The effects of high-fat feeding on trabecular bone observed in our study were modest compared to changes reported by others [12, 13, 32]. We speculate that some of the differences between studies may be accounted for by specific aspects of the diet (e.g., 45% fat content vs. 60%), differences in species (e.g., rat vs. mouse), or differences in genetic makeup within a species (e.g., BALB/c vs C57BL/6 mice).…”
Section: Discussioncontrasting
confidence: 97%
“…Although obesity induced increases in body mass can act as growth factor on bone through augmented mechanical loading, high-fat diets can increase osteoclastogenesis, marrow adipogenesis, and decrease bone mass [12, 14]. Consumption of high-fat diets also increases circulating levels of the hormone leptin, a principal regulator of energy homeostasis that can impact bone growth [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vast majority of studies have instead focused on the detrimental effects of high-fat diet feeding on skeletal homeostasis. In general, these studies have reported a reduction in bone mass secondary to reduced osteoblast activity and increased osteoclastic bone resorption (46)(47)(48)(49), as well as reduced sensitivity to anabolic hormones such as parathyroid hormone (PTH) (50).…”
Section: Discussionmentioning
confidence: 99%